Tryptophan Metabolites as Biomarkers for Esophageal Cancer Susceptibility, Metastasis, and Prognosis - Chen, Yun; Chen, Jianliang; Guo, Dainian; Yang, Peixuan; Chen, Shuang; Zhao, Chengkuan; Xu, Chengcheng; Zhang, Qiuzhen; Lin, Chaoxian; Zhong, Shilong; Zhang, Shuyao (Frontiers in Oncology, 2022)
Background Perturbation of tryptophan (TRP) metabolism contributes to the immune escape of cancer; however, the explored TRP metabolites are limited, and their efficacy in clarifying the susceptibility and progression of esophageal cancer (EC) remains ambiguous. Our study sought to evaluate the effects of the TRP metabolic profile on the clinical outcomes of EC using a Chinese population cohort; and to develop a risk prediction model targeting TRP metabolism. Method A total of 456 healthy individuals as control subjects and 393 patients with EC who were followed up for one year as case subjects were enrolled. Quantification of the plasma concentrations of TRP and its metabolites was performed using HPLC-MS/MS. The logistic regression model was applied to evaluate the effects of the subjects’ clinical characteristics and plasma metabolites on susceptibility and tumor metastasis events, whereas Cox regression analysis was performed to assess patients’ overall survival (OS). Results Levels of creatinine and liver enzymes were substantially correlated with multiple metabolites/metabolite ratios in TRP metabolism, suggesting that hepatic and renal function would exert effects on TRP metabolism. Age- and sex-matched case-control subjects were selected using propensity score matching. Plasma exposure to 5-HT was found to be elevated 3.94-fold in case subjects (N = 166) compared to control subjects (N = 203), achieving an AUC of 0.811 for predicting susceptibility event. Subsequent correlation analysis indicated that a higher plasma exposure to 5-HIAA signiﬁcantly increased the risk of lymph node metastasis (OR: 2.16, p = 0.0114). Furthermore, it was figured out that OS was significantly shorter for patients with elevated XA/KYN ratio (HR: 1.99, p = 0.0016), in which medium and high levels of XA/KYN versus low level had a significantly lower OS (HR: 0.48, p = 0.0080 and HR: 0.42, p = 0.0031, respectively). Conclusion This study provides a pivotal basis for targeting endogenous TRP metabolism as a potential therapeutic intervention.